A reflective exploration of international academic exchanges: Analysing impacts and envisioning transformative international learning experiences - Tiao, Wei-Jie; Yokokawa, Akira; Majd, Mahsa (LPMPP Universitas Negeri Yogyakarta, 2024)
The phenomenon of international mobility has emerged as a prominent aspect of higher education internationalization worldwide. However, it is crucial to recognize that the essence of internationalization extends beyond the sheer number of international students enrolled. A pivotal focus lies in the multicultural competencies these students cultivated during their extended residence and study abroad periods. This empirical study endeavors to ascertain the genuine accomplishments of international students concerning multicultural exploration and the development of a global mindset while pursuing degrees overseas. Key considerations encompass the daily experiences of these students in communities with diverse cultures, their adaptation to academic life on campus amidst classmates and professors from various cultural backgrounds, and the evolution of their multicultural competencies and global perspectives. Through critical reflection, this paper presents a conceptual framework to enhance comprehension of multicultural competencies within the context of higher education's internationalization trends. The research methodology involved qualitative interviews conducted with international students in Taiwan, and the ensuing data underwent analysis using content analysis techniques. The findings underscore the intricate nature of multicultural competencies in higher education, encompassing multiple processes and challenges. To foster more successful international study experiences, this study advocates for collaborative efforts from host institutions and peers alongside international students' comprehensive understanding of the host country's culture.